1981
DOI: 10.1139/v81-327
|View full text |Cite
|
Sign up to set email alerts
|

Absolute rate constants for hydrocarbon autoxidation. 30. On the self-reaction of the α-cumylperoxy radical in solution

Abstract: Can. J. Chem. 59.2253 (1981. Although it is generally accepted that the self-reaction of cumylperoxy radicals is a second-order process, recent reports have cast doubt on the overall validity of this assumption. Therefore we have reinvestigated some aspects of the self-reaction to clarify the kinetic and mechanistic features.Our product studies are entirely consistent with the accepted mechanism for the self-reaction of cumylperoxy radicals and no evidence was obtained for competing reactions. Results obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Phenyl benzoate was prepared from benzoyl chloride and I phenol. 2,2,3,3-Tetraphenylbutane and di-tert-butyl hyponitrite 1 had been prepared previously in our laboratory (1). Phenol, , acetophenone, benzophenone, and I, 1-diphenylethanol were commercially available and were purified by standard methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenyl benzoate was prepared from benzoyl chloride and I phenol. 2,2,3,3-Tetraphenylbutane and di-tert-butyl hyponitrite 1 had been prepared previously in our laboratory (1). Phenol, , acetophenone, benzophenone, and I, 1-diphenylethanol were commercially available and were purified by standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…Phenol, , acetophenone, benzophenone, and I, 1-diphenylethanol were commercially available and were purified by standard methods. : Product studies Oxidation and decomposition products were identified by a combination of gc-ms and hplc techniques as described previously (1). Yields of most of the oxygenated products were determined by reverse-phase hplc and were accurate to -+ 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for self-reaction of tertiary alkylperoxyls has been well estabished (2)(3)(4). These radicals exist in dynamic equilibrium with a tetroxide which decomposes to give two caged alkoxyls and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…These radicals exist in dynamic equilibrium with a tetroxide which decomposes to give two caged alkoxyls and oxygen. A fraction (-10%) of these alkoxyls combine to give di-tert-alkyl peroxide while the remainder escape the solvent cage and undergo H-atom abstraction, p-scission, or rearrangement (3,4).…”
Section: Introductionmentioning
confidence: 99%